The Use of Social Media as a Marketing Strategy for Bank Syariah Indonesia (BSI) in Improving Brand Image - Amini, Zakiyah; Anggraini, Cindy; Hendra, Joni (Journal of Business Inflation Management and Accounting, 2025)
This study aims to analyze the marketing strategy of Bank Syariah Indonesia (BSI) in utilizing social media to improve brand image. This study uses a qualitative approach by collecting secondary data from BSI's social media posts and relevant online articles. The results show that BSI's marketing strategy through social media includes education and information, customer interaction and engagement, social promotion and CSR, customer testimonials and reviews, influencer-based promotions, consistency in branding, use of paid advertising, and analysis and measurement. Factors that influence the effectiveness of this strategy include content quality, consistency, interaction, with users, use, influencers, planned promotions, use of attractive visuals, performance analysis and monitoring, community involvement, online reputation, technological innovation, market segmentation, and adaptation to trends. The positive impacts of social media use for BSI include increasing brand awareness, strengthening reputation and trust, direct interaction with customers, promotion of new products and services, market analysis and monitoring, image enhancement, humanism, strengthening relationships with the community, and public education about Islamic banking. This study suggests that BSI continue to develop their digital strategy to maintain and improve their brand image in the future.